G52(P) The Rapid Eczema Severity Score (RESS). (7th April 2014) - Fujitani, S; Lomas, D; Roberts, N; Solman, L; Syed, S; Thanopoulou, I; Koutoumanou, E; Kinsler, V; Glover, M; Harper, J
Abstract : Background: Eczema is a common inflammatory dermatosis, with a rising incidence and significant effect on the quality of life for the child and the family. Known validated scoring systems are time consuming and not always practical in the clinic setting. The RESS is a rapid numeric assessment which includes questions on overall severity (0–10), pruritus (0–10) and sleep disturbance (0–7). There was in addition a question on current treatment, grouped one to four. Aims: The aim was to compare the RESS with the Patient-Oriented Eczema Measure (POEM), the Children's Dermatology Life Quality Index (CDLQI) and the Infants' Dermatitis Quality of Life Index (IDQOL) in a busy clinical unit, by evaluating the correlation between these scores and clinical outcomes. Objectives: To audit the performance and practicality of the RESS in our clinical practice, compared to the POEM, the CDLQI and the IDQOL. Method: This was a questionnaire based study comparing the different scoring systems measured simultaneously in a busy tertiary referral Paediatric Dermatology department. Subjects were 158 children with eczema. Results: Spearman rank correlations of the severity scores of RESS and POEM (r = 0.775, p < 0.001), RESS and CDLQI (r = 0.673, p < 0.001) and RESS and IDQOL (r = 0.751, p < 0.001) were moderate to strong. There were statistically significant reductions in the median percentage of total scores for each of the RESS, POEM, CDLQI (p < 0.001) and IDQOL (p = 0.001) at the follow-up visit as assessed by the Wilcoxon signed rank test, indicating that therapy was effective, and scoring systems were comparable both before and after therapy. Inter-observer reliability was high [ICC=0.965 95% confidence interval (CI) 0.930–0.984]. Clinicians consistently rated the RESS as the easiest to use in a clinical setting. Conclusions: The RESS is a valid and reliable method of assessing severity when compared to existing scoring systems in our clinical practice, and was the easiest to use in a busy clinical setting.